The Role Of Toba Batak Cultural Philosophy In The World Of Education In North Tapanuli District - Sibarani, Sariayu; Dewi, Izwita; Simamora, Elmanani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
There are many tribes in Indonesia and each tribe has its own uniqueness. However, this uniqueness certainly has a value that is considered important for each follower. The unique values of each tribe influence various aspects in the lives of the individuals in that tribe. The Toba Batak ethnic group has a cultural philosophy to guide their lives. To achieve this philosophy they carry out education because they are aware that education is a step in achieving this philosophy. The Toba Batak tribe has many life philosophies or life guidelines. One such philosophy is Anakkon Hi Do Hamoraon in Ahu. The research method used in this research is descriptive qualitative. This research aims to: examine the cultural philosophy of the Toba Bataks in North Tapanuli in shaping the mindset of the Toba Batak ethnic group regarding the importance of education. This research has 2 objectives, namely: 1). Knowing the condition of education in North Tapanuli, and 2). Knowing the role of Toba Batak cultural values in community education in North Tapanuli. The research was carried out by conducting field observations, literature studies and in-depth interviews with three types of sources, namely: government, community leaders and the community. The research results were analyzed using qualitative descriptive methods. The research results show the role of local cultural values in increasing public awareness of obtaining education. Through education, society achieves 3 main ideals, namely hamoraon, hagabeon and hasangapon so that society is taken into account in daily life and in cultural activities. The cultural value of anakkon ki do hamoraon in ahu has a unique educational significance. The community is invited to strive to obtain education for their children accompanied by the aspiration that their children's lives must be of a higher quality than their own lives, which can only be achieved by obtaining a good education. These cultural values also motivate students to study and excel in school.